Balloon borne Antarctic frost point measurements and their impact on polar stratospheric cloud theories - Rosen, James M.; Hofmann, D. J.; Carpenter, J. R.; Harder, J. W.; Oltsmans, S. J. (1988)
Balloon-borne frost point measurements were performed over Antarctica during September-October 1987 as part of the NOZE II effort at McMurdo. The results show water mixing ratios on the order of 2 ppmv in the 20 km region, suggesting that models of the springtime Antarctic stratosphere should be based on approximately 2 ppmv water vapor. Evidence indicating that some PSCs form at temperatures higher than the frost point in the 15 to 20 km region is discussed. This supports the binary HNO3-H2O theory of PSC composition.